Leadership and Work Environment Mediated by Work Motivation to Employee Performance at Ar-Risalah Surakarta Foundation - Dwi Henri Wijiatmoko; Ida Aryati; Sarsono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to investigate the influence of leadership style, work environment and work motivation to employees performance. In addition, this research is also to investigate work motivation as a mediating factor between leadership style, work environment, and employee performance. The study encompasses of 180 employees, with a sample size of 64 respondents selected through purposive sampling. Primary data were collected using a questionnaire. The findings reveal that leadership style lacks a positively and significantly impacts employees performance. While work environment positively and significantly influences employees performance. Additionally, work environment affects positively and significantly to work motivation. Furthermore, work environment positively and significantly affects employee performance. The study also indicates that leadership style positively and significantly influences employee performance through work motivation, and similarly, work environment has a positive and significant impact on employee performance through work motivation.